The Role Of Fashion Involvement As A Mediator Between Shopping Lifestyle And Hedonic Shopping Motivation On Shopee Users' Buying Impulse In Bandar Lampung - Nurhadi, Nurhadi; Febriansyah, Febriansyah (Jurnal Ekonomi, 2024)
The existence of impulsive behavior has a positive impact on business actors, especially in the fashion industry, because it can increase profits and accelerate the purification of goods in the fashion world; some trends will continue to roll with the times. This study examines the influence of Shopping lifestyle, Hedonic Shopping Motivation on impulse buying, and the role of Fashion Involvement in the influence of Shopping lifestyle Hedonic Shopping Motivation on buying impulse. This type of research is quantitative research. The primary data source used in the sampling technique is purposive sampling. The sample used was 100 samples. The data analysis technique used is Structural Equation Modelling. Based on the results of the study, it can be concluded that the shopping lifestyle variable affects the impulse buying variable, the hedonic shopping motivation variable affects the impulse buying variable, the fashion involvement variable can issue the Shopping lifestyle variable to the impulse buying variable and the fashion involvement variable cannot issue the Shopping lifestyle variable to the impulse buying variable.